Quasi come uno animale: splendor and drifting of the composition term (2011)
This article attempts a reflection on the drifting of the composition-term in scope of: 1) The relationship between nature and art by Aristotle. 2) The pregnancy of Composition in classicist Aesthetics. 3) The Critics of Classicism by Kant based on his notion of Reflective Aesthetical Judgement. 4) The consequence of the break of minimal art with naturalism and anthromorphic structures present in Art-History.